Use of Complementary and Alternative Medicine: A survey in Turkish Gastroenterology Patients - Kav Taylan (BMC, 2009)
Abstract Background The study examined complementary and alternative medicine (CAM) usage by patients attending a Turkish gastroenterology outpatient clinic. Methods The survey was conducted on 216 patients presenting with gastrointestinal problems during their first visit to the clinic using a 31 item, self-report questionnaire between May and October 2005. Data included information on patient demographics and their gastrointestinal symptoms, as well as items to identify CAM use and patient satisfaction with these therapies. Results Seventy-nine patients (36.6%) reported using one or more forms of CAM. The most commonly used therapy was herbal therapy, usually taken as a tea or infusion. These were used by 27 people (29%) in this subgroup. Common indicators for their use were epigastric pain, constipation, bloating and dyspepsia or indigestion. CAM use among upper GI patients was marginally higher than lower GI patients (41.8% versus 41.2%), but the highest usage was amongst patients with liver disease where 53.8% reported using one or more CAM therapy. About half of the patients learned about CAM from their relatives or friends, with more women than men using the therapies (p < 0.05). Clinical characteristics such as diagnosis, duration of symptoms and prior surgical intervention did not differ between users and non-users of CAM therapies. Multivariate analysis showed that being female and higher educational status were positively associated with CAM usage (p < 0.05). Conclusion CAM usage in our sample of gastrointestinal patients was lower than that described in other countries and other chronic disease groups. This could be due to their low perceived efficacy, or the relatively transient duration of symptoms experienced by the sample. Healthcare professionals need however, to be aware of CAM usage in order to educate patients appropriately about possible adverse effects or drug-interactions.